Structure and properties of the wollastonite–calcium phosphate coatings deposited on titanium and titanium–niobium alloy using microarc oxidation method - Sedelnikova M. B. Mariya Borisovna; Sharkeev Yu. P. Yury Petrovich; Khlusov I. A. Igor Albertovich; Komarova E. G. Ekaterina Gennadjevna; Chebodaeva V. V. Valentina Vadimovna (2016, 2016)
Title screen